Prognostic impact of clinician-based interpretation of 18F-fluorodeoxyglucose positron emission tomography/computed tomography reports obtained in patients with newly diagnosed diffuse large B-cell lymphoma. Issue 7 (July 2014) - Mylam, Karen J.; El-Galaly, Tarec C.; Hutchings, Martin; Brown, Peter; Himmelstrup, Bodil; Gerke, Oke; Gillstrøm, Dorte; Sillesen, Ida B.; Munksgaard, Lars; Pedersen, Bjarne B.; Christiansen, Ilse; Jensen, Paw; et al.
Abstract The aim of this study was to evaluate the prognostic value of clinician interpretation of positron emission tomography/computed tomography (PET/CT) reports at mid-therapy, interim PET (I-PET) and after the end of first-line therapy (E-PET) in patients with diffuse large B-cell lymphoma (DLBCL). Four hundred and thirty patients were enrolled in this study comprising a total of 617 PET reports. Each report was evaluated by three expert hematologists randomly selected from a panel of nine. Reports were labeled positive or negative if all three interpreters agreed. All others were considered indeterminate. Indeterminate reports accounted for 59% of I-PET and 49% of E-PET reports. Two-year overall survival (OS) for patients with a positive, indeterminate and negative I-PET was 58%, 87% and 89% (p < 0.001), respectively. Two-year OS for patients with E-PET was 41%, 89% and 97% (p < 0.001) for positive, indeterminate and negative interpretation of PET/CT reports. Progression-free survival and OS did not differ significantly in patients with a negative and an indeterminate I-PET report. The use of well-defined reporting criteria, e.g. the Deauville five-point scale, is likely to reduce the number of scans perceived as indeterminate.